2020
DOI: 10.1002/jmv.26719
|View full text |Cite
|
Sign up to set email alerts
|

Saliva for diagnosis of SARS‐CoV‐2: First report from India

Abstract: There are very few studies in search of an alternate and convenient diagnostic tool which can substitute nasopharyngeal swab (NPS) specimen for detection of SARS‐CoV‐2. In the study we analyzed, the comparison and agreement between the feasibility of using the saliva in comparison to NPS for diagnosis of SARS‐CoV‐2. A total number of 74 patients were enrolled for this study. We analyzed and compared the NPS and saliva specimen collected within 48 h after the symptom onset. We carried out real‐time quantitative… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“… In children <12 years old with signs and symptoms compatible with COVID-19, we suggest the use of NAAT in nasopharyngeal swab samples versus NAAT in saliva samples for diagnosis of COVID-19. Weak against Very low [ 90 , 94 , 95 , 99 , 103 , 107 , 108 , 114 , 115 , 117 ] 25 In patients ≥12 years old with signs and symptoms compatible with COVID-19, should saliva sampling be used, compared with nasopharyngeal swab sampling for diagnosis of COVID-19 with NAAT? In patients ≥12 years old with signs and symptoms compatible with COVID-19, we suggest the use of NAAT in nasopharyngeal swab samples versus NAAT in saliva samples for diagnosis of COVID-19.…”
Section: Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“… In children <12 years old with signs and symptoms compatible with COVID-19, we suggest the use of NAAT in nasopharyngeal swab samples versus NAAT in saliva samples for diagnosis of COVID-19. Weak against Very low [ 90 , 94 , 95 , 99 , 103 , 107 , 108 , 114 , 115 , 117 ] 25 In patients ≥12 years old with signs and symptoms compatible with COVID-19, should saliva sampling be used, compared with nasopharyngeal swab sampling for diagnosis of COVID-19 with NAAT? In patients ≥12 years old with signs and symptoms compatible with COVID-19, we suggest the use of NAAT in nasopharyngeal swab samples versus NAAT in saliva samples for diagnosis of COVID-19.…”
Section: Recommendationsmentioning
confidence: 99%
“… In patients with signs and symptoms compatible with COVID-19 at risk for severe illness, we suggest the use of NAAT in nasopharyngeal swab samples versus NAAT in saliva samples for diagnosis of COVID-19. Weak against Very low [ 13 , [90] , [91] , [92] , [93] , [94] , [95] , [96] , [97] , [98] , [99] , [100] , [101] , [102] , [103] , [104] , [105] , [106] , [107] , [108] , [109] , [110] , [111] , [112] , [113] , [114] , [115] , [116] , [117] , [118] ] a Strength of recommendation (strong against, weak against, in research only, weak for, strong for). b Overall certainty of the evidence (high, moderate, low, very low).…”
Section: Recommendationsmentioning
confidence: 99%
“…Although our results showed that, in general, saliva is less sensitive when compared to NPS and OPS, the collection of these two respiratory specimens are not an easy or an ideal method for widespread screening and may be associated with various degrees of discomfort for the patient [31]. This can be more dangerous for patients having thrombocytopenia or any other coagulation disorder [32], in which the sample collection can cause bleeding.…”
Section: Discussionmentioning
confidence: 72%
“…Evidence related to using saliva for SARS-CoV-2 testing is evolving, and recent studies have reported promising results [4, 5]. Unfortunately, saliva-based tests in India are explored by very few studies [5, 6].…”
Section: Introductionmentioning
confidence: 99%